Socially preferable and technically feasible: European citizens choose solar power and import independence over lower costs - Tröndle, Tim; Mey, Franziska; Lilliestam, Johan (Energy Research & Social Science, 2025)
Citizen's preferences about decarbonised electricity supply are crucial for a successful energy transition, both regarding the direction and the speed at which it can unfold. While preferences about single aspects, like prices and technology, have been assessed before, these preferences cannot be directly translated to preferred energy supply on the system level, for two reasons: First, the individual aspects interact and cannot be assessed in isolation. Varying the technology mix, for example, affects many other aspects of the electricity system such as prices. Second, many aspects have both local and global impacts and cannot be assessed for just a single region. Constraining imports in one region, for example, affects the technology mix in other regions. Therefore, preferences can only be meaningfully analysed within consistent scenarios that incorporate multiple aspects including their interactions, are able to represent the local context, and have a broad spatial scope. Such scenarios are out of scope of pure preference studies. Here, we overcome these limitations by combining preference data with detailed techno-economic scenarios on the national and subnational scale. Building on random utility theory, we fit a discrete choice model to data from a choice experiment conducted in four European countries and use it to predict choices of scenarios. We find that citizens would choose scenarios with high shares of local self-sufficiency and solar power over trade- and wind-power-centered least-cost scenarios, although they are more expensive. Our approach allows to evaluate energy plans not only by technical and economic aspects, but also by citizen preferences.
CRIS-Team Scopus Importer:2025-10-16